Integration of Islam and Education - Syah, Yoshy Hendra Hardiyan; Badrudin, Badrudin; Ulfiah, Ulfiah (Jurnal Iman dan Spiritualitas, 2024)
This article examines the integration of Islam and education. The objective of this article is to understand the importance of education in life and explore the relationship between religion and education. The research method employed is qualitative descriptive with the data collection technique of literature review, using an interdisciplinary approach to understand the educational context from the perspective of Islam in order to describe the integration of Islam and education descriptively. What makes this article interesting is its emphasis on the significance of education in life and the revelation of the relationship between religion and education. The research findings highlight that through the provision of education, individuals gain an understanding of the meaning and purpose of life, enabling them to experience the sweetness of life with everything it encompasses. Conversely, individuals without a foundation of education may lack awareness of the meaning and purpose of life, leading to a lack of satisfaction and happiness. Furthermore, the relationship between religion and education is depicted as mutually reinforcing, where religion serves as the most crucial foundation for education. Education grounded in religion, according to the article, gives rise to a distinctive meaning. Islam views education as a right for everyone, regardless of gender, and it is considered a lifelong process. Within the realm of education, Islam is seen as a source of inspiration with a complex and clear formulation in terms of goals, curriculum, methods, teachers, facilities, and more.